Motivation of students with learning disorders in memorizing alfiyah ibn malik at imadutthulabah islamic boarding school - Anzar Aquil; Aliwan; Ahmad Mustafidin; Santi Ratnawati; Kunfuaidah Latifah; Maskur (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research examines the motivation of students with learning disorders in memorizing the Alfiyah Ibnu Malik book verses at Pondok Pesantren Imadutthulabah. The study aims to understand both intrinsic and extrinsic motivation, as well as the supporting and inhibiting factors faced by these students. Using a phenomenological approach and descriptive qualitative method, this research collected data through interviews with the head of the boarding school, the Alfiyah book verse listeners, Nahwu Shorof subject teachers, and students with learning disorders. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, with data validity checks using source triangulation and method triangulation. Intrinsic motivation, such as personal satisfaction, a sense of achievement, personal development, and responsibility, plays a crucial role in supporting students. This motivation comes from an internal drive to understand and master knowledge, encouraging students to keep trying even though it requires more effort and time. Extrinsic motivation is also important, including external support like praise, expectations from others, and rewards, which encourage students to be more enthusiastic and persistent in their learning. The inhibiting factors faced include genetic, neurobiological, and environmental factors. This study reveals that despite the challenges, students with learning disorders demonstrate resilience and adaptability through various coping strategies. The findings highlight the need for tailored educational interventions and continuous support systems to maximize the students’ potential in Islamic boarding school environments.